The implementation of an integrated language skills method to improve standardized test results. (2022)
The Saber tests; Saber Pro and Saber 11, are State Examinations of Quality for the Evaluation of Education, (ECAES), which are applied at the level of Higher and Secondary Education, in Colombia. Even though, it is a test that assesses different professional and social skills, the English Module does not address the four comprehensive skills - reading, writing, listening and speaking. Therefore, through this thesis project, an Instructional design is presented that focuses on the presentation of teaching and learning strategies to be addressed in undergraduate students of the Santo Tomás University, this design has been piloted in 35 students at Gimnasio de los Cerros, its goal is towards educational and favorable achievement in the Saber Tests, in the English Module. The scheme of the Common European Framework of Reference for Languages (CEFR) is taken into account, with the reference of the competences that must be developed in the students, which correspond to the linguistic, pragmatic and sociolinguistic competence and; the elements from International Tests of English as a foreign language , such as the TOEFL iBT and the Cambridge exams. Methodologically, the Curriculum Design for higher education is taken into account, in light of the improvement of the academic processes of the students, from the deployment and analysis of the Saber Tests, identifying the benefits and areas of opportunity. Furthermore, with the didactic proposal, curricular strategies are reflected with their respective evaluation system. Finally, the results, conclusions and suggestions for the implementation of the educational proposal are exposed, which must attend the four linguistic abilities in an integral way.